Pre-existing Proton Pump Inhibitor Treatment and Short-Term Prognosis of Acute Myocardial Infarction Patients - Xie, Juntao; Chen, Qingui; He, Dejian (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Evidence suspects proton pump inhibitor (PPI) use is risk factor of poor prognosis of acute myocardial infarction (AMI). We aimed to investigate the association between pre-existing PPI use before emergency department (ED) visit and short-term prognosis of AMI patients. Materials and methods: AMI patients admitted to ED were included and categorized as cohorts with or without pre-existing PPI use. Hospital mortality, length of hospital stay, being admitted to intensive care unit (ICU), and length of (total) ICU stay were studied as prognostic outcomes. Multivariable logistic regression or linear regression were used to estimate the associations between pre-existing PPI use and the outcomes after adjusting for potential confounders. Results: 2001 AMI patients were included. No significant difference was found in hospital mortality and length of ICU stay between cohorts; patients with pre-existing PPI use showed a significantly longer length of hospital stay (median 3.81 versus 3.20 days, P=0.002) but lower proportion of being admitted to ICU (25.59% versus 40.83%, P<0.001) compared to those without pre-existing PPI use. Pre-existing PPI use was not associated with hospital mortality (odds ratio (OR) 1.08, 95% confidence interval (CI) 0.58-1.99), length of hospital stay (β=0.23, 95% CI -0.35 to 0.82), and length of ICU stay (β=-0.18, 95% CI -1.06 to 0.69), but was statistically significantly associated with lower risk of being admitted to ICU (OR 0.69, 95% CI 0.52-0.92). Conclusion: The current study does not support newly diagnosed AMI patients with pre-existing PPI use before ED visit would experience worse short-term prognosis than those without.